Age-Related Macular Degeneration Etiology, Diagnosis and Management - A Glance at the Future - Lo Giudice, Giuseppe (IntechOpen, 2013)
Age-related macular degeneration (AMD) is the leading cause of irreversible central vision loss in developed countries.There have been rapid developments of therapies that today can halt or even reverse aspects of vision loss resulting from AMD among those most severely affected, and there is promise of future therapies that may prevent vision loss. This book provides an overview about AMD; an update on the current understanding of AMD, pathophysiology, the use of diagnostic tests, the management of both non-neovascular and neovascular AMD as well as future directions in treatment and its limitations. It also looks into the future with potential treatment options that are now under investigation in clinical trials.